SISTEM PEMERINTAHAN NEGERI DI PULAU AMBON DAN PULAU-PULAU LEASE (1824-2008) - Rina Pusparani; Nuraida Kubangun; Efilina Kissiya (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2017)
Government land on the island of Ambon and Lease Islands experienced changes very significantly in each period. For this study wanted to see how the development of the State Government in Central Maluku in the early 20th century until 1942. To get an answer to problems above do research using the historical method consists of four stages: heuristics, external and internal criticism, interpretation and historiography. In analyzing the dta applied to some of the concepts and theories of other social sciences to get a historical explanation. The results of this study concluded that the rules regulating government turns the country on the island of Ambon and Lease Islands is not just limited to 2004 because there are rules issued by the local government to better explain the procedures for land administration system on the island of Ambon and Lease Islands. From 1824 until now there have been changes in the lowest administration system in Indonesia, including Maluku, causing conflict between communities within a country on the island of Ambon and Lease Islands. For the archives of these rules will respont the problems that have been faced by people in Maluku.